The Effect of Tanespimycin (17-AAG) on Radioiodine Accumulation in Sodium-Iodide Symporter Expressing Cells - Yu, Kyoung Hyun (Springer-Verlag, 2012)
PURPOSE: The heat shock protein 90 inhibitor, tanespimycin, is an anticancer agent known to increase iodine accumulation in normal and cancerous thyroid cells. Iodine accumulation is regulated by membrane proteins such as sodium iodide symporter (NIS) and pendrin (PDS), and thus we attempted to characterize the effects of tanespimycin on those genes. METHODS: Cells were incubated with tanespimycin in order to evaluate (125)I accumulation and efflux ability. Radioiodine uptake and efflux were measured by a gamma counter and normalized by protein amount. RT-PCR were performed to measure the level of gene expression. RESULTS: After tanespimycin treatment, (125)I uptake was increased by ∼2.5-fold in FRTL-5, hNIS-ARO, and hNIS-MDA-MB-231 cells, but no changes were detected in the hNIS-HeLa cells. Tanespimycin significantly reduced the radioiodine efflux rate only in the FRTL-5 cells. In the FRTL-5 and hNIS-ARO cells, PDS mRNA levels were markedly reduced; the only other observed alteration in the levels of NIS mRNA after tanespimycin treatment was an observed increase in the hNIS-ARO cells. CONCLUSIONS: These results indicate that cellular responses against tanespimycin treatment differed between the normal rat thyroid cells and human cancer cells, and the reduction in the (125)I efflux rate by tanespimycin in the normal rat thyroid cells might be attributable to reduced PDS gene expression.